Prediction of Insolvency of Hungarian Micro Enterprises (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The aim of the study is to establish insolvency forecast model with the usage of different statistical methods and compare their efficiency. Besides this the relation and direction between indebtedness and financial distress is also part of the examination. With different approaches we nearly reached the same efficiency, the main focus was on the independent testing sample where we did not apply any modification on the dataset supposing realistic circumstances for predicting the probability of default. The research is focusing on small companies, since their number in the economy is considered high, but for this segment such insolvency forecasts are very rare.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.